Lubrication of piston ring in natural gas reciprocating compressor - 282801 Muhamad Elyas Musa (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal) - Universiti Teknologi Malaysia, 2005